Concretes based on composite cements with the addition of granulated blast furnace slag and cement dust - Leonid Dvorkin; Vadim Zhitkovsky (Zaštita Materijala)
A set of experimental-statistical models has been obtained that makes it possible to predict the workability and strength of concrete on a composite binder, including the addition of dust from cement clinker kilns and granulated blast-furnace slag, as well as polycarboxylate superplasticizer Sika VC 225. The values of the critical water-cement ratio are determined, which determine the area of constant water demand and take into account the binder normal consistency, as well as the adsorption coefficients of fine and coarse aggregates. Experimental-statistical models of the coefficients that determine the yield of concrete strength per 1 kg of composite cement and Portland cement Cem I contained in it are obtained.